Breast cancer patients' satisfaction with individual therapy goals and treatment in a standardized integrative medicine consultancy service - Hack, Carolin; Antoniadis, Sophia; Hackl, Janina; Langemann, Hanna; Schwitulla, Judith; Fasching, Peter; Beckmann, Matthias; Theuser, Anna-Katharin (Archives of Gynecology and Obstetrics, 2018)
PURPOSE: Complementary medicine services are nowadays usually quite heterogeneous, and little information is available on standards for running an integrative medicine consultancy service. This study aimed to assess patients' satisfaction with a standardized treatment service on integrative medicine. METHODS: Using a cross-sectional design, 75 breast cancer patients from the integrative medicine consultancy service at the University Breast Center for Franconia were evaluated between January 2016 and March 2017. At primary consultation, patients answered a standardized questionnaire on their medical history and treatment goals regarding integrative medicine. In a subsequent interview, patients evaluated their satisfaction with the treatment service and individual treatment goals. RESULTS: 72% of the patients (n = 54) reported high satisfaction with the overall approach of the treatment service. 76% of the patients (n = 57) were very satisfied or satisfied with their individual treatment plans. The most frequently reported goals were to slow tumor progression (n = 64, 85.3%), reducing the side effects of conventional cancer treatments (n = 60, 80%), and a desire to participate actively in the treatment of breast cancer (n = 64, 85.3%). CONCLUSIONS: Using a standardized procedure in integrative medicine allows a high quality level to be offered to patients. Overall, breast cancer patients report very high satisfaction with the integrative medicine consultancy service and state long-term treatment goals. Hence, long-term treatment with integrative medicine methods should be taken into consideration.
EVALuna2:209947